2009
DOI: 10.1017/s0007114509991474
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged refeeding improves weight maintenance after weight loss with very-low-energy diets

Abstract: The aim of the present study was to test the hypothesis that a prolonged refeeding duration after successful very-low-energy diet (VLED)-induced weight loss beneficially affects weight development and eating behaviour. Patients (n 269) were recruited to a 1-year obesity treatment programme with 12 weeks of an initial VLED. After the VLED, patients with $ 10 % weight loss were randomly allocated to 1 week (group 1) or 6 weeks (group 6) refeeding to an ordinary, energy-reduced diet, and thereafter followed and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Eight of the studies used a strict VLCD, ie, no other food was allowed except for the VLCD powder mixed with water (6, 7, 10, 11, 20, 22, 23, 25). In 7 of the studies, the participants were allowed to consume vegetables (1217, 19), and in 2 of the studies the powder formulas were mixed with milk (26) or a small ad libitum breakfast was allowed within the 800-kcal/d limit (31).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the studies used a strict VLCD, ie, no other food was allowed except for the VLCD powder mixed with water (6, 7, 10, 11, 20, 22, 23, 25). In 7 of the studies, the participants were allowed to consume vegetables (1217, 19), and in 2 of the studies the powder formulas were mixed with milk (26) or a small ad libitum breakfast was allowed within the 800-kcal/d limit (31).…”
Section: Resultsmentioning
confidence: 99%
“…For 18 months 55% of self-guided individuals were maintaining their weight loss within 2.3 kg, as compared to 13% of VLCD. Gripeteg et al 26 reported that after successful very low energy diets (VLED) inducing weight loss ≥ 10%, patients with six weeks of re-feeding maintained a significantly greater weight loss (regained: 3.9 ± 9.1%) over one year of treatment than patients with only one week of re-feeding (regained: 8.2 ± 8.3%, P = 0.006). Accordingly, it was suggested that ordinary foods should be re-introduced slowly to enhance weight control after a VLED period.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual reintroduction of food following a LED or VLED is believed to assist with weight loss maintenance (Leeds 2014;Brown et al 2015). For example, research has shown that reintroducing food over a 6week period resulted in significantly less weight regain at 52 weeks compared with a reintroduction period of 1 week (3.9 kg vs. 8.2 kg, respectively) (Gripeteg et al 2010). In addition, reintroducing food over 6 weeks was associated with increased dietary restraint (the tendency to eat less than desired) and reduced external eating (the tendency to eat in response to external cues such as the sight of food) compared to reintroduction lasting only 1 week.…”
Section: Weight Maintenance Following Very Lowenergy and Low-energy Fmentioning
confidence: 99%